Methodology of Domain Specific Mathematical Modelling - Mezhuyev, Vitaliy (2014)
The methodology of Domain Specific Mathematical Modelling (DSMM), which implementation aims to overcome the shortcomings of the existing methodology of Domain Specific Modelling is proposed. The levels of the metamodelling architecture and the formal semantics of the DSMM metamodels are defined. The examples of the DSMM application for development of the metamodels for modelling various domains are considered.